Single- and repeat-dose toxicity of IDX14184, a nucleotide prodrug with antiviral activity for hepatitis C viral infection, in mice, rats, and monkeys. (May 2016) - Luo, S; Rush, R; Standring, D
The single- and repeat-dose toxicity profile of IDX14184, a novel guanosine nucleotide prodrug with antiviral activity against hepatitis C viral infection, was characterized following once daily oral administration for durations up to 13, 26, and 32 weeks in mouse, rat, and cynomolgus monkey, respectively. The heart, liver, kidney, skeletal muscles, and lower gastrointestinal tract (cecum, colon, and/or rectum) were identified as the primary toxicity targets in these nonclinical species. The mouse was relatively insensitive to IDX14184-induced cardiac toxicity and hepatotoxicity. The rat was very sensitive to IDX14184-induced skeletal muscle, liver, heart, and lower gastrointestinal tract toxicity but relatively insensitive to kidney toxicity. The monkey is a good animal species to detect IDX14184-induced toxicity in the cardiac and skeletal muscles, and in the liver and kidney, but not lower gastrointestinal tract toxicity. The toxicity profile of IDX14184 was most appropriately characterized in rats and monkeys. The conduct of a series of cardiac size and function assessments during a non-rodent toxicology study using echocardiography proved great utility in this work. IDX14184 clinical development was eventually terminated due to suboptimal efficacy and regulatory concerns on potential heart and kidney injury in patients, as seen with a different guanosine nucleotide prodrug, BMS-986094.